Enhancing Efl Learners' Critical Thinking Through Human Communication And Human Discussion Activities In The Era Of Ai - Amina Berrarbi; Nadia Amrane (The Journal of Studies in Language, Culture and Society)
This study investigates the role of human communication and discussion activities in fostering critical thinking among EFL learners, particularly in an era increasingly influenced by artificial intelligence (AI). While AI-powered tools offer language learners unprecedented access to information and automated feedback, they often lack the humanistic and interactive dimensions essential for developing higher-order thinking skills. This research examines how face-to-face discussions and communicative activities can complement AI-based learning by enhancing students' ability to analyze, evaluate, and articulate ideas critically. The study was conducted with a sample of 100 undergraduate EFL students and 6 instructors at Djillali Liabes University, Algeria. A mixed-method approach was employed, using questionnaires, interviews, and classroom observations to explore students' engagement in discussion-based learning. Findings reveal that while AI tools support certain aspects of language acquisition, students struggle with expressing ideas critically, engaging in debates, and developing autonomous reasoning. Teachers also highlighted the importance of balancing AI-driven instruction with interactive human communication to cultivate critical thinking skills effectively. This research underscores the necessity of integrating discussion-based activities alongside AI-assisted learning to foster both linguistic proficiency and cognitive development in EFL students.